MAQASHID SHARIA THINKING PERSPECTIVE OF IBNU ASSYUR IN THE DEVELOPMENT OF SHARIA BANKING - Lifia Lifia; Aunur Rofiq (Journal of Management and Informatics, 2023)
Ibn Asyur was the second originator who made the concept of Maqashid Syariah into all scientific disciplines after Al Syathabi, in line with the journey of maqashid Syariah to become a field of knowledge. Sharia banking is also the second concept after the presence of conventional banking, but that is not a thing that prevents Islamic banking from continuing to grow and develop to spread benefits. Ibnu Asyur in his thoughts conveyed the similarity between maqashid sharia and the main objective of establishing sharia banking. Maqashid sharia in the perspective of Ibn Asyur can produce indicators of growth and development of sharia banking to be very rapid and of course still useful for Muslims and humanity in general.